CORRELATION BETWEEN LOCAL BONE DENSITY AND INSERTION TORQUE AS PREDICTORS OF IMMEDIATE IMPLANT LOADING. A BIBLIOGRAPHIC REVIEW - Ortega-Martínez, Jordi (British Journal of Healthcare and Medical Research, 2021)
Title: Correlation between local bone density and insertion torque as predictor of immediate implant loading. A bibliographic review. Background: Implants have become an alternative to rehabilitate lost teeth. One of the prerequisites for immediate loading is to determine primary stability by analyzing bone density and insertion torque. Aims: A bibliographic review is conducted to correlate local bone density and insertion torque as predictors of the immediate loading of an implant. Materials and methods: Review using PubMed databases of systematic reviews, meta-analyses, randomized clinical studies, non-randomized clinical studies, in vitro studies, cohort studies, cross-sectional studies, and clinical trials, either in English or in Spanish. The focus was on the correlation between local bone density and insertion torque. Results: Local bone density is a useful guide for determining insertion torque and predicting initial implant stability. Discussion: The insertion torque and bone density values determine whether immediate loading of the implant is possible or not, and therefore predict this possibility. Conclusions: A correlation between local bone density and insertion torque was established, and this correlation predicts immediate loading of an implant. Therefore, to reach a consensus, further studies should consider all the factors influencing this concept.